Joyful Learning in Elementary Mathematics: A Multi-Site Case Study of Teacher Strategies and Student Engagement in Tomohon City - Deysti Trivena Tarusu; Junita C. Makawawa; Navel Oktaviandy Mangelep (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines the challenges of implementing Joyful Learning in primary school mathematics instruction across four public schools in Tomohon City, North Sulawesi, addressing the gap between national curriculum policy endorsement of student-centered pedagogy and its actual classroom practice. Methods: A qualitative multi-site case study design was employed involving 12 mathematics teachers and 60 students across urban and peripheral schools. Data were collected through 48 classroom observations, semi-structured interviews, lesson plan (RPP) analysis, school assessment reports, and a student engagement questionnaire, analyzed using Miles and Huberman's (2014) interactive model. Findings: Only 25% of observed lessons incorporated joyful elements (40% urban vs. 10% peripheral schools). Student engagement averaged 2.3 out of 5.0, with 65% reporting persistent confusion and average achievement scores of 65/100. Research Implications: Effective Joyful Learning requires sustained mathematics-specific teacher professional development, equitable resource allocation, and structured community engagement programs. Policymakers should develop ready-to-use joyful mathematics modules aligned with Kurikulum Merdeka objectives and establish dedicated infrastructure funding for peripheral schools. Originality: This study provides the first multi-site empirical evidence of Joyful Learning implementation in a mid-sized Indonesian city, revealing how urban-peripheral resource disparities systematically determine pedagogical innovation outcomes at the primary school level.